Synthesis of a Pentacene‐Type Silaborin via Double Dehydrogenative Cyclization of 1, 4‐Diboryl‐2, 5‐disilylbenzene. Issue 28 (6th June 2016) - Hirofuji, Tatsuya; Ikeda, Toshiaki; Haino, Takeharu; Yamamoto, Yohsuke; Kawachi, Atsushi
Abstract: A new pentacene‐type silaborin, in which three benzene rings are bridged by silicon and boron atoms, has been synthesized and characterized by using NMR spectroscopy and X‐ray crystallographic analysis. The precursor, 1, 4‐bis(dimesitylboryl)‐2, 5‐bis(phenylsilyl)benzene (4 ), was prepared by stepwise introduction of a silyl group and a boryl group to a benzene ring starting from 1, 4‐dibromobenzene. Double cyclization of4 proceeds by a H‐Mes exchange and a B‐H/C‐H dehydrogenative condensation to afford pentacene‐type silaborin5 . X‐ray crystal structure analysis reveals that5 adopts a bent structure rather than a planar one. UV/Vis spectra and DFT calculations for5 reveal a lowering of the LUMO energy level compared with corresponding anthracene‐type3 . Abstract : Double the fun ! A double cyclization that includes hydrogen–mesityl (H‐Mes) exchange and B‐H/C‐H dehydrogenative condensation affords the new pentacene‐type silaborin, in which three benzene rings are bridged by silicon and boron atoms (see scheme).